2015
DOI: 10.5194/acp-15-12011-2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dust particle internal structure on light scattering

Abstract: Abstract. There is a large variety of internal structures inside atmospheric dust particles, making them inherently inhomogeneous. Such structures may have a large effect on ground-level and atmospheric radiation. So far, dust particle internal structures and their effect on the light scattering properties have proved to be hard to quantify, in part due to challenges in obtaining information about these structures. Recently, internal structures of individual dust particles were revealed through focused ion bea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Several experimental and remote sensing studies have shown that any reasonable distribution of nonspherical particles is superior compared to the spherical particles used by Mie theory when it comes to optical properties of mineral dust (see Nousiainen, 2009, and references therein). Especially, the dust nonsphericity is extensively studied and applied in lidar investigations (e.g., Ansmann et al, 2017;Gaststeiger et al, 2011;Jeong et al, 2016;Kemppinen et al, 2015). However, dealing with nonsphericity is not a completely resolved issue in dust forecast models as most models are still based on the Mie theory.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental and remote sensing studies have shown that any reasonable distribution of nonspherical particles is superior compared to the spherical particles used by Mie theory when it comes to optical properties of mineral dust (see Nousiainen, 2009, and references therein). Especially, the dust nonsphericity is extensively studied and applied in lidar investigations (e.g., Ansmann et al, 2017;Gaststeiger et al, 2011;Jeong et al, 2016;Kemppinen et al, 2015). However, dealing with nonsphericity is not a completely resolved issue in dust forecast models as most models are still based on the Mie theory.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, clays and iron oxyhydroxides are 10 intimately associated (cemented) with the coarser quartz and feldspar grains (see SEM and TEM results below). This is a very important finding due to the effect that internal mixing (i.e., aggregates) of clays plus iron oxyhydroxides surrounding larger silicate mineral grains has on the radiative properties of desert dust (Sokolik and Toon, 1999;Formenti et al, 2014b;Kemppinen et al, 2015;Zhang et al, 2015;Jeong et al, 2016). Abundant quartz along with small amounts of feldspars, and abundant clay minerals were detected in the silt fraction ( Fig.…”
Section: Xrd Analysis: Linking Mineralogy With Potential Dust Source mentioning
confidence: 87%
“…While some researchers consider that the net radiative forcing of mineral dust on the climate system is negative (GierĂ© and Querol 2010;Allen et al, 2016), others report that under specific scenarios the direct forcing can be positive (Carlson and Benjamin, 1980), leading to regional (Overpeck et al, 1996) or even global warming (Kok et al, 2017). The uncertainties regarding the sign and magnitude of the direct radiative forcing of desert dust are rooted in the fact that they depend on many poorly 20 constrained factors such as: (i) the characteristics of mineral dust (concentration, vertical distribution, PSD, shape, internal/external mixing, and composition/mineralogy) and (ii) external variables such as surface albedo below dust plumes, temperature at ground level, and presence/absence of clouds (Balkanski et al, 2007;Kemppinen et al, 2015). Composition/mineralogy and particle size, as well as mixing state, appear to be the most critical factors controlling dust direct radiative forcing (Zhang et al, 2015).…”
Section: Effects Of Mineralogy Mixing State and Psd On Dust Direct mentioning
confidence: 99%
“…The mixing rule approximation used to calculate effective optical constants for composite particle could be another source of uncertainty. The validity of the effective optical constants has been discussed in several studies including Liu et al (2014), Mishchenko et al (2014), Kahnert (2015), Kemppinen et al (2015), and Mishchenko et al (2016). Common finding of the studies was that the effective-medium approximation (EMA) could be reasonable when a large number of small inclusions were evenly distributed in a host mineral particle with small refractive-index contrast between the host and inclusion minerals.…”
Section: Uncertainty Analysismentioning
confidence: 99%